Polymorphism in the Mitochondrial Cytochrome B of Crossbred Madura-Limousine Cattle - Rimayanti, Rimayanti; Utomo, Budi; Pradana, Dilasdita Kartika; Triana, Indah Norma; Akintunde, Adeyinka Oye; Mustofa, Imam (Archives of Veterinary Science, 2023)
Madura cattle breeders in rural Indonesia prefer to request artificial insemination services for their cows with Limousin bull’s freeze-thawed semen. However, crossbred Madura-Limousin (Madrasin) bulls reported a high infertility rate. This study aimed to identify the mutation of cytochrome b (Cytb) mtDNA in Madura-Limousin crossbred cattle to develop a fundamental breeding approach that would promote animal protein production and preserve the genetics of purebred Madura cattle. Blood samples were collected from the two bulls of crossbred Madura-Limousin, purebred Madura, and Limousin bulls for DNA analysis. The polymerase chain reaction was used to amplify the Cytb mtDNA, which was then sequenced using the Sanger method. The MEGA 7.0 software was used with the neighbor-joining method to construct the phylogenetic tree. Compared to the purebred Madura cattle and purebred Limousin bulls, the crossbred Madura-Limousin bulls (also known as Madrasin) exhibited alterations in their nucleotide sequence as follows: Deletion of Adenine (number 37), mutation Guanine (66) to Cytosine, Thymine (73) to Cytosine, Guanine (78) to Adenine, Cytosine (84) to Guanine, Thymine (85) to Cytosine, Thymine (99) to Cytosine, Adenine (105) to Guanine, Adenine (114) to Guanine, Cytosine (126) to Thymine, Cytosine (141) to Thymine, and Adenine (144) to Cytosine, resulting in corresponding changes in the deletion of amino acid Isoleucine (position number 11) and mutation of Isoleucine (34) to Methionine. As observed in the resulting clades, the purebred Madura and Limousin cattle were grouped, while Madrasin crossbred cattle were separated. It could be concluded that Madrasin bulls exhibited alterations in their nucleotide and protein sequences of Cytb mtDNA, placing them in a distinct group from purebred Madura cattle and Limousin bulls.